2020
DOI: 10.1016/j.jpaa.2020.106389
|View full text |Cite
|
Sign up to set email alerts
|

Projective normality of torus quotients of flag varieties

Abstract: Let G = SL n (C) and T be a maximal torus in G. We show that the quotient T \\G/P α1 ∩ P α2 is projectively normal with respect to the descent of a suitable line bundle, where P αi is the maximal parabolic subgroup in G associated to the simple root α i , i = 1, 2. We give a degree bound of the generators of the homogeneous coordinate ring of T \\(G 3,6 ) ss T (L 2̟3 ). For G is of type B 3 , we give a degree bound of the generators of the homogeneous coordinate ring of T \\(G/P α2 ) ss T (L 2̟2 ) whereas we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In [3], Howard et al showed that the GIT quotient of G 2,n by T with respect to the descent of O ( n 2 ) (respectively, O (n)) is projectively normal if n is even (respectively, if n is odd). In [14], Nayek et al used graph theoretic techniques to give a short proof of the projective normality of the GIT quotient of G 2,n by T with respect to the descent of O (n) for any n.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], Howard et al showed that the GIT quotient of G 2,n by T with respect to the descent of O ( n 2 ) (respectively, O (n)) is projectively normal if n is even (respectively, if n is odd). In [14], Nayek et al used graph theoretic techniques to give a short proof of the projective normality of the GIT quotient of G 2,n by T with respect to the descent of O (n) for any n.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], the authors used combinatorial method to show that T \\(G 2,n ) ss T (L(nω 2 )) is projectively normal with respect to the descent of the line bundle L(nω 2 ) for n is odd. In [19], the authors used graph theoretic technique to give a short proof of the projective normality of T \\(G 2,n ) ss T (L(nω 2 )) for general n. In [10], authors studied the torus quotients of Schubert varieties in orthogonal grassmannians. Authors showed the following: when G = Spin(8, C) the GIT quotient of G/P α4 is projectively normal with respect to the descent of the ample line bundle L(2ω 4 ) and isomorphic to the projective space P 2 .…”
Section: Introductionmentioning
confidence: 99%